Is There a Classical Inertial Sublayer Over the Amazon Forest?. Issue 10 (30th May 2019) - Dias‐Júnior, Cléo Quaresma; Dias, Nelson Luís; dos Santos, Rosa Maria N.; Sörgel, Matthias; Araújo, Alessandro; Tsokankunku, Anywhere; Ditas, Florian; de Santana, Raoni Aquino; von Randow, Celso; Sá, Marta; Pöhlker, Christopher; Toledo Machado, Luiz Augusto; et al.
Abstract: On the basis of measurements over different surfaces, an inertial sublayer (ISL), where Monin‐Obukhov Similarity Theory applies, exists above z =3 h, where h is canopy height. The roughness sublayer is within h < z <3 h . Most studies of the surface layer above forests, however, are able to probe only a narrow region above h . Therefore, direct verification of an ISL above tall forests is difficult. In this study we conducted a systematic analysis of unstable turbulence characteristics at heights from 40 to 325 m, measured at an 80m, and the recently built 325‐m Amazon Tall Tower Observatory towers over the Amazon forest. Our analyses have revealed no indication of the existence of an ISL; instead, the roughness sublayer directly merges with the convective mixed layer above. Implications for estimates of momentum and scalar fluxes in numerical models and observational studies can be significant. Plain Language Summary: The Amazon forest interacts with the atmosphere by emitting and absorbing many substances, such as carbon dioxide, methane, ozone, and organic compounds, produced by the vegetation. These substances are very influential in both the regional and global climates, and until now, the estimates of their emission and absorption rates are based on classical theories developed originally over relatively short vegetation and valid for a region above the ground called the "inertial sublayer." In this work we present evidence, obtained with the help of measurements from a very tall tower (325 m), that a classical inertial sublayer does not exist over the Amazon forest. New methods to quantify the emission and absorption rates, therefore, will be needed to improve their estimates. Key Points: Measurements made from 40 to 325 m above the Amazon Forest do not show evidence of an inertial sublayer The roughness sublayer directly merges with the mixed layer under daytime unstable conditions New methods and theories will be needed to address the nonexistence of the inertial sublayer to estimate fluxes over the Amazon forest